Characterization of Cancer Stem Cells in Moderately Differentiated Buccal Mucosal Squamous Cell Carcinoma - Yu, Helen H.; Featherston, Therese; Tan, Swee T.; Chibnall, Alice M.; Brasch, Helen D.; Davis, Paul F.; Itinteang, Tinte (Frontiers in Surgery, 2016)
Aim To identify and characterize cancer stem cells (CSC) in moderately differentiated buccal mucosa squamous cell carcinoma (MDBMSCC). Methods 4μm-thick formalin-fixed paraffin-embedded MDBMSCC samples from six patients underwent 3,3-diaminobenzidine (DAB) immunohistochemical (IHC) staining for the embryonic stem cell (ESC) markers NANOG, OCT4, SALL4, SOX2 and pSTAT3; cancer stem cell marker CD44; squamous cell carcinoma (SCC) marker EMA; and endothelial marker CD34. The transcriptional activities of the genes encoding NANOG, OCT4, SOX2, SALL4, STAT3 and CD44 were studied using NanoString gene expression analysis and colorimetric in situ hybridization (CISH) for NANOG, OCT4, SOX2, SALL4 and STAT3. Results DAB and immunofluorescent (IF) IHC staining demonstrated the presence of (1) an EMA+/CD44+/SOX2+/SALL4+/OCT4+/pSTAT3+/NANOG+ CSC subpopulation within the tumor nests; (2) an EMA-/CD44-/CD34-/SOX2+/OCT4+/pSTAT3+/NANOG+ subpopulation within the stroma between the tumor nests; and (3) an EMA-/CD44-/CD34+/SOX2+/ SALL4+/OCT4+/pSTAT3+/NANOG+ subpopulation on the endothelium of the microvessels within the stroma. The expression of CD44, SOX2, SALL4, OCT4, pSTAT3 and NANOG was confirmed by the presence of mRNA transcripts, using NanoString analysis and NANOG, OCT4, SOX2, SALL4 and STAT3 by CISH staining. Conclusion This study demonstrated a novel finding of three separate CSC subpopulations within MDBMSCC: (1) within the tumor nests expressing EMA, CD44, SOX2, SALL4, OCT4, pSTAT3 and NANOG; (2) within the stroma expressing SOX2, SALL4, OCT4, pSTAT3 and NANOG; and (3) on the endothelium of the microvessels within the stroma expressing CD34, SOX2, SALL4, OCT4, pSTAT3 and NANOG.